2016
DOI: 10.1136/injuryprev-2016-042027
|View full text |Cite
|
Sign up to set email alerts
|

Girls crash too: trends in single vehicle crash rates in young and adult, male and female drivers

Abstract: Young adult drivers (YADs) are over-represented in crashes mainly because of their age and inexperience. Studying single vehicle crashes by age and sex may identify new approaches to intervention. In 2014, male YAD (17-19 years) crash casualty rates were 11.4 times higher than older drivers (30-59 years), compared with 17.6 times higher in 2005, and 1.9 times female YAD, compared with 2.5 times higher in 2005. Crash casualty rates involving male and female YADs are declining. Action is needed to address YAD cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In our cohort, men were at higher risk of certain types of crash and were twice as likely as women to be involved in a single vehicle crash. This affirms previous research that has identified men at higher risk of single vehicle crashes ( Amarasingha & Dissanayake, 2014 ; Bingham & Ehsani, 2012 ; Brown et al, 2014 ; Jones, 2017 ; Tsai et al, 2008 ). A hypothesized explanation for this is that single vehicle crashes result from increased risk-taking behaviour, for example overtaking in a single lane road or speeding, that men are more likely to engage in than women ( Jiménez-Mejías et al, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our cohort, men were at higher risk of certain types of crash and were twice as likely as women to be involved in a single vehicle crash. This affirms previous research that has identified men at higher risk of single vehicle crashes ( Amarasingha & Dissanayake, 2014 ; Bingham & Ehsani, 2012 ; Brown et al, 2014 ; Jones, 2017 ; Tsai et al, 2008 ). A hypothesized explanation for this is that single vehicle crashes result from increased risk-taking behaviour, for example overtaking in a single lane road or speeding, that men are more likely to engage in than women ( Jiménez-Mejías et al, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…As drivers, young men have long been known to be at increased risk of crash compared to young women and older drivers ( Amarasingha & Dissanayake, 2014 ; Jones, 2017 ). Our results build on these established sex differences and demonstrate that this increased risk does not diminish as men get older and gain more driving experience through the early to middle years of adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have addressed sex or gender differences in population-based rates of road crash injury or death, with higher values usually observed in men [ 1 , 2 , 3 , 4 , 5 , 6 ], specifically in drivers’ risk of road crash or crash-related injury or death. In fact, there is consistent evidence showing increased male-to-female ratios in this context [ 7 , 8 , 9 , 10 , 11 , 12 ], although this pattern seems to change with age, with higher risk values found in men, especially at younger ages [ 11 , 13 , 14 , 15 , 16 ]. Furthermore, conflicting findings arise when specific issues, such as injury severity, are considered (i.e., depending on whether death or serious injury is considered as the outcome, the risk may be higher for men or for women in different studies) [ 3 , 8 , 17 ].…”
Section: Introductionmentioning
confidence: 97%